Serum Calcium Concentrations, Chronic Inflammation and Glucose Metabolism: A Cross-Sectional Analysis in the Andhra Pradesh Children and Parents Study (APCaPS). Issue 3 (25th October 2018) - Shridhar, Krithiga; Kinra, Sanjay; Gupta, Ruby; Khandelwal, Shweta; D, Prabhakaran; Cox, Sharon E; Dhillon, Preet K
Abstract: Background: Evidence suggests a role for elevated serum calcium in dysregulated glucose metabolism, linked through low-level chronic inflammation. Objectives: We investigated the association of elevated serum calcium concentrations (corrected for albumin) with markers of dysregulated glucose metabolism and type II diabetes and tested if these associations were accounted for by chronic inflammation in a rural Indian population. Methods: A cross-sectional analysis of participants aged 40–84 y from the Andhra Pradesh Children and Parents Study (APCaPS; n  = 2699, 52.2% women) was conducted. Comprehensive information on household, sociodemographic, and lifestyle factors; medical and family history; physical measurements; blood measurements including fasting plasma glucose (FPG), fasting insulin (FI), serum calcium, albumin, phosphorous, vitamin D (in a subset), and creatinine were analyzed. Additionally, in a random sample of healthy participants ( n  = 1000), inflammatory biomarkers (interleukins 6 and 18, soluble intercellular adhesion molecule 1, adiponectin, and high-sensitivity C-reactive protein) were measured and an inflammatory score (IScore) calculated. Results: After adjustments for sociodemographics, lifestyle factors, and anthropometry the highest calcium quartile (Q4 compared with Q1) was associated with FI (β = 1.4 µU/ml; 95% CI: 1.2, 1.5 µU/ml; P -trend < 0.001), the homeostasis model assessment for insulin resistance (HOMA-IR) (β = 1.4; 95% CI: 1.2, 1.5; P -trend < 0.001), and was modestly associated with FPG (β = 2.1 mg/dL; 95% CI: −0.9, 5.2 mg/dL; P -trend = 0.058) and prevalent type II diabetes (OR = 1.6; 95% CI: 1.0, 2.6; P -trend= 0.020). In the healthy subgroup, the association of the highest calcium quartile was similar for FI and HOMA-IR. Additional adjustment with IScore did not alter the associations. Further, in a subset, all these associations were independent of endogenous regulators of calcium metabolism (serum vitamin D, phosphorus, and creatinine). Independently, after accounting for potential confounders, the highest IScore quartile (Q4 compared with Q1) was positively associated with FPG, FI, HOMA-IR, and prevalent prediabetes, and also with serum calcium concentrations in men. Conclusions: Elevated serum calcium was positively associated with markers of dysregulated glucose metabolism and prevalent type II diabetes in a rural Indian population. Chronic inflammation did not mediate this association but was independently associated with markers of dysregulated glucose metabolism. Inflammation might be responsible for elevated serum calcium concentrations in men.